2011
DOI: 10.3892/or.2011.1346
|View full text |Cite
|
Sign up to set email alerts
|

Gastric cancer and concomitant renal cancer: A systematic immunohistochemical and molecular analysis

Abstract: Abstract. The frequency of gastric cancer in patients with renal cell carcinoma (RCC) is exceptionally high in our region suggesting a common molecular basis. Our study aimed to characterize tumors and to analyze possible underlying molecular features in 12 patients with gastric cancer and concomitant RCC. We performed an immunohistochemical analysis including p53 protein expression, proliferative activity (MIB-1), mismatch repair status (hMLH1, hMSH2, hMSH6, PMS2) and E-cadherin expression in gastric cancers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…In line with reporter assay, we observed a strong decrease of KRAS expression in presence of miR-433 mimics, whereas the scramble had no effects in HGC-27 cells (Figure 4c). Previous studies have shown the importance of the KRAS/ERK signaling pathway in the regulation of cell migration, invasion and metastasis [1517]. To investigate whether miR-433 could affect GC cell phenotype through the KRAS/ERK pathway, we examined the phosphorylation level of ERK in HGC-27 cells overexpressing miR-1433.…”
Section: Resultsmentioning
confidence: 99%
“…In line with reporter assay, we observed a strong decrease of KRAS expression in presence of miR-433 mimics, whereas the scramble had no effects in HGC-27 cells (Figure 4c). Previous studies have shown the importance of the KRAS/ERK signaling pathway in the regulation of cell migration, invasion and metastasis [1517]. To investigate whether miR-433 could affect GC cell phenotype through the KRAS/ERK pathway, we examined the phosphorylation level of ERK in HGC-27 cells overexpressing miR-1433.…”
Section: Resultsmentioning
confidence: 99%